Age‐related health care disparities in multiple myeloma. Issue 1 (21st April 2017) - Puyade, Mathieu; Defossez, Gautier; Guilhot, François; Leleu, Xavier; Ingrand, Pierre
Abstract: Age is a well‐known factor in solid tumours linked to lower adherence to guidelines. Scarce data exist for haematologic malignancies such as multiple myeloma (MM). The aim of the study was to investigate the relationships among age, adherence to guidelines in MM, and overall survival (OS).The Poitou‐Charentes cancer registry has exhaustively registered incident cases of MM from 2008 to 2010. Diagnosis, staging, prognosis, and first‐line treatment were compared to the international guidelines. Three hundred and sixty‐seven patients aged 36 to 93 years were included. Compliance to diagnostic procedure was 98%, staging 62%, prognosis 30%, and first‐line treatment 89%. Cytogenetic analysis was compliant in 37%. Younger age was the strongest factor associated with compliant provision of care (odds ratio 14.4 [6.1‐33.8] for <66 years and 2.3 [0.9‐6.1] for 66‐74 years; P < .0001). The second independent factor was active versus smouldering myeloma (odds ratio 3.5 [1.6‐7.3]; P = .0009). Adherence to guidelines is related with OS in multivariate analysis hazard ratio: 1.6 [1.0‐2.5]; P = .03. Age is linked with inadequate provision of care in myeloma, particularly prognosis and first‐line treatment. Compliance to guidelines seems to be related to OS taking into account the main prognostic factors. Future guidelines should stress the point that age and frailty need to be taken into account in myeloma care.